UPAYA KERJA SAMA ASEAN DAN CHINA DALAM MENGATASI JUDI ONLINE - Ghazani, Fachrul; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The rise of cross-border online gambling activities has created significant security challenges for the Southeast Asian region. This study addresses the research questions concerning the forms of cooperation between ASEAN and China in responding to transnational crimes particularly online gambling and the reasons behind ASEAN’s decision to collaborate with China. To answer these questions, this research employs a qualitative method using document analysis by examining ASEAN policy frameworks, China’s cooperation commitments, UNODC reports, national regulations, and academic literature related to cybercrime and online gambling. The findings reveal that ASEAN collaborates with China due to the extensive involvement of cross-border criminal networks operating across the region, the increasing technological sophistication of online gambling platforms, and the fact that many operational centers and digital infrastructures are connected to China and its economic spheres. This cooperation materializes through mechanisms such as the AMMTC and various Joint Statements that emphasize intelligence sharing, joint enforcement operations, and strengthened digital regulation. The study concludes that such cooperation emerges from a shared need to address regional security threats that no single state can resolve alone, thereby requiring stronger coordination, policy harmonization, and enhanced law enforcement capacity across Southeast Asia. Keywords : ASEAN, China, international cooperation, online gambling, transnational crime